Development of polymorphic microsatellites for the invasive Asian fish tapeworm Schyzocotyle acheilognathi. Issue 3 (June 2018) - Brabec, Jan; Scholz, Tomáš; Štefka, Jan
Abstract: We describe the development of ready-to-use set of fifteen polymorphic microsatellite markers to benefit future population biology and phylogeographic studies on the invasive Asian fish tapeworm Schyzocotyle acheilognathi . The microsatellite loci were selected from partial Illumina shotgun genome sequences of three parasite specimens and their universality tested on a set of 12 geographically distant populations of the parasite. Particularly low levels of heterozygosity have been detected in the Chinese population pointing towards possible hidden population structure that deserves further attention in future population genetic studies.